Knowledge, Attitudes and Practices on Adolescent Vaccination among Parents, Teachers and Adolescents in Africa: A Systematic Review Protocol - Abdullahi, Leila H.; Kagina, Benjamin M.; Cassidy, Tali; Wiysonge, Charles S. (Vaccine, 2016)
Vaccines are the most successful and cost-effective public health interventions available to avert vaccine-preventable diseases and deaths. Despite global progress in adolescent health, many adolescents in Africa still get sick and die from vaccine-preventable diseases due to lack of vaccination. Adolescents, parents and teachers are key players in the development and implementation of adolescent vaccination policies. Optimal knowledge, attitudes and practices towards adolescent vaccination among these key players may improve vaccine uptake among adolescents. We conducted a qualitative and quantitative systematic review on knowledge, attitudes and practices of adolescent vaccination among adolescents, parents and teachers in Africa. We searched PubMed, Cochrane Central Register of Controlled Trials, Scopus, Web of Science, WHOLIS, Africa Wide and CINAHL for eligible quantitative and qualitative primary studies with no time limits. We also checked reference lists of included studies for eligible studies and searched grey literature. Two authors independently screened the search outputs, selected studies and extracted data; resolving discrepancies by consensus and discussion. Qualitative data were analysed using thematic analyses where applicable, while analyses from quantitative studies used different methods based on the type of outcomes. We included 18 cross-sectional studies in this review. The included studies were conducted in 10 out of the 54 countries in Africa. The 18 studies focused on a wide range of adolescent vaccines. Thirteen studies evaluated vaccines against Human Papilloma Virus, while each of the remaining 5 studies, evaluated vaccines against rabies, HIV, tetanus toxoid, tuberculosis and adolescent vaccines in general. Among the key players, we found low to moderate levels of knowledge about adolescent vaccination. Positive attitudes and practices towards adolescent vaccination, especially against Human Papilloma Virus were reported. Despite the low knowledge, our results showed high levels of acceptability to adolescent vaccination among adolescents, parents and teachers. It was evident in our review that all key demographics (parents, adolescents and teachers) were receptive towards adolescent vaccines. We propose relevant policy makers in Africa to consider continuous education programs such as those aimed to inform the parents, adolescents and teachers on adolescent vaccination.
Keywords: Adolescents; Parents; Teachers; Knowledge